Implementasi Absensi SIAP (Sistem Informasi Absensi Pegawai) pada Dinas Perindustrian dan Perdagangan Kabupaten Karawang - Putri, Amanda Auliana; Rismayadi, Budi; Pertiwi, Wike (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
Along with the development of science and technology in the era of globalization, various applications on smartphones aim to make it easier for users, especially during the COVID-19 pandemic, where many companies implemented work-from-home (WFH) policies, fieldwork and official employees leaving the city. So there is a problem with employee attendance because usually attendance is only done in the office. This research aims to: determine the implementation of SIAP Attendance (Employee Attendance Information System) at the Karawang Regency Industry and Trade Service. The method used in this research is descriptive qualitative using the Triangulation Technique. The sample used was 5 people, using observation and interviews. The research results show that SIAP Attendance can improve an employee's attendance discipline, because this attendance system uses GPS technology, so superiors can know the employee's location when taking attendance.